Bacteria cellulose from A.xylinum fermentation using hydrolysate of banana-peel waste as carbon source - Akil, Mustapha (2011)
The high cost of utilizing commercial sugar as carbon source in bacterial cellulose (BC) production has become an issue in the industry. Discovery or alternative carbon source from cheap sources. e.g. agricultural (food) waste is needed to overcome this problem. Two key objectives are set in this study. namely (i) to investigate the reducing sugar yield obtained from the diluted acid hydrolysis or agricultural (food) waste and (ii) to synthesize and characterize BC using hydrolysate obtained in (i) as the carbon source. Sago effluent, potato peel and banana peel were selected as raw material. The dilute acid hydrolysis method was used to hydrolyze these wastes. Three hydrolysis parameter, sulphuric acid concentration (2%, 4% and 6%). reaction time (20, 40 and 60 minutes) and temperature (105°C and 121°C) were studied. The highest glucose yield for each waste's hydrolysate was used in the fermentation experiment to screen the best carbon source for BC production. Hydrolysis of potato produced the highest glucose yield, i.e. 43.44 mg/ml using 4% (v/v) acid at 20 minutes reaction time and 121°C reaction temperature. The highest glucose yield, i.e. 19.15°C from banana peel hydrolysis was obtained after 20 minutes using 6% (v/v) of acid at 121°C whilst for sago effluent, as reaction time was extended to 40 minutes using 4% (v/v) acid at 105°C, only 2.64 mg/ml or glucose was obtained. Banana peel hydrolysate was selected as the carbon source used in this study because it produced the highest yield or BC, i.e. 2.89 g/l after 21 days of incubation period compared to other hydrolysate. For the selection or the suitable initial pi I and initial carbon source concentration, it was found that initial pH 6 and 2.0% of carbon source concentration produced 2.81 g/l or BC after 16 days incubation. SEM analysis shows that BC has ultrafine fibrils and a pore-like reticulated structure. TGA result show that BC was rapidly degraded at 250°C. The existence of common functional group i.e OH group. C=O group. C-H bending. C-H stretching. C-H wagging. C-C stretching. C-O-C vibration and c-o stretching confirms the purity of BC. From BET and BJH analysis. BC has mesopore range of porosity with maximum pore size of 24.629A during adsorption and 19.070A for desorption process. The total surface area of the BC was 10.891 m2/g. Investigation or tensile strength shows that BC has maximum tensile stress and Young's modulus values at 55.84 MPa and 773.61 MPa. respectively. In conclusion. this study provides information on converting agricultural (food ) waste into fermentable sugar via dilute acid hvdrolysis where it can be utilized for BC production.